Comparison of Awareness of Eye Donation among Medical and Paramedical Students - Jayashree MP; Chaitra Pujar; Vidya Rudrappa Gadag; Mallikarjun Salagar; Monalisha Pattnaik (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2017)
Purpose: To compare the awareness of eye donation and willingness to donate eyes among medical and paramedical students. Materials and Methods: This is a cross sectional study undertaken in April 2016, among 200 first and second year medical students and 200 BSc nursing students of S Nijalingappa Medical Collage, Bagalkot. A semi-structured questionnaire was self-administered for collecting the necessary information after  getting informed consent. The questionnaire was on demographic profile, their awareness on eye donation, sources of information and willingness to donate eyes. Results: Awareness of organ donation noted was 100 % among medical students and 90% among paramedical students. Mass media such as TV, newspaper, poster, magazine were important sources of information for both groups.93% of medical students thought the ideal time duration to retrieve eyes is within 6 hours after death and 83% paramedical students gave the correct answer. Paramedical students thought communicable disease and blood group are barriers for eye donation. Willingness to donate eyes was similar in both the groups. Conclusion: The awareness of eye donation is better in medical students compared to paramedical students, but most of the students in both groups were inclined to pledge for eye donation.